Abusive Swearing Variations in the Temanggung Javanese Dialect: Type and Social Reality - Ira Mayasari; Ahmad Muzaki (Universitas Indraprasta PGRI, 2019)
Abstract: This study aims to describe the types of Temanggung dialect Javanese language curses, as well as their functions in social life. The analysis in this study uses sociolinguistic studies. The method of data collection is carried out by means of competent listening because it is in the form of observation and observation, and is assisted with oral and written data. The results of this study are found in several types of swear, including swear based on limb 10, swear animal name 4, swear profession name negative 1, part 1 tree, no swear referent 32, intelligence 2 condition, and mental health 4. The most common types of swear are swear no referents because sometimes swear forms do not have an original word and are formed conventionally in each region. Thus, swearing in each region certainly varies according to the agreement of the area. Based on its function, in this study found 7 functions, namely the means to express anger, resentment, disappointment, wonder, regret, insult and familiarity.